Networks of CD8+ T Cell Response Activation in Melanoma and Vitiligo - Fukuda, Keitaro (Frontiers in Immunology, 2022)
Melanoma is an aggressive skin cancer derived from melanocyte, which shows high response rate to cancer immunotherapy, such as immune checkpoint inhibitors (ICIs). Vitiligo is an autoimmune skin disease resulting from the destruction of melanocytes by autoreactive CD8+ T cells. Vitiligo induced by cancer immunotherapy is a favorable prognostic factor in patients with melanoma, and growing evidence supports the fact that melanocyte/melanoma-shared antigen (MSA)-specific CD8+ T cells infiltrated in the tumor (melanoma) and skin (vitiligo) microenvironment play pivotal roles in the prognosis of both diseases. Thus, cellular communications that promote MSA-specific CD8+ T cells recruitment, proliferation, and effector functions are now seen as key targets to enhance the efficacy of current therapies for both diseases. Here, we discussed recent advancements in illustrating immune signaling pathways and immune cell types that regulate migration, proliferation, and function of MSA-specific CD8+ T cells in melanoma and vitiligo; and future immunotherapeutic approaches that may enhance clinical outcomes of both diseases.